The Effectiveness of the Index Card Match Learning Model in Improving Mathematics Learning Outcomes on Plane Figures - Hasanah, Miftakhul; Praptiningsih, Praptiningsih; Sugiyat, Sugiyat (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
The limited number of studies on the effectiveness of the Index Card Match (ICM) learning model in lower elementary school classes, particularly on the topic of plane figures forms the basis of this research, despite the significant implications for early mathematical concept comprehension. This study aims to analyze the effectiveness of the ICM model in improving the mathematics learning outcomes of second-grade students on the topic of plane figures and to identify student participation levels during the learning process. A quantitative method with a posttest-only control group design was employed, involving 67 students from MI Muhammadiyah Trangsan selected through purposive sampling. Data were collected using multiple-choice learning outcome tests and student engagement observation sheets, and analyzed using descriptive statistics and independent sample t-tests. The results show a significant difference between the experimental group (mean score of 92.5) and the control groups (mean scores of 68 and 63), with a significance value of 0.021 (p < 0.05). These findings reinforce the constructivist theories of Piaget and Vygotsky, which emphasize the importance of interaction and direct experience in active learning. The main conclusion of this study is that the application of ICM significantly enhances students’ mathematics learning outcomes across cognitive, affective, and psychomotor domains. The implications include contributions to the development of active learning strategies in lower elementary classrooms and practical recommendations for teachers to adopt ICM as an innovative, enjoyable, and effective method. This research also opens opportunities for further exploration of ICM application across different subjects and educational levels, including its development through interactive technology.